Antioxidant activity of twenty wild Spanish Thymus mastichina L. populations and its relation with their chemical composition - Delgado, Teresa (2018)
The antioxidant activity and chemical composition of essential oils and methanolic extracts of twenty Spanish Thymus mastichina L. populations were studied. Both essential oils and methanolic extracts possessed antioxidant properties. However, the total phenol contents of the methanolic extracts varied between 2.90 and 9.15mg GAE/g extract and the EC 25 values of DPPH free radical scavenging activity between 0.90 and 3.45mg/mL for the methanolic extracts and 78-241mg/mL for essential oils, these showing low antioxidant potential. Actually, in essential oils the main compound determined was the 1,8-cineole (56.8-69.6%), whereas thymol, γ-terpinene, terpinolene and geraniol (species with considerable DPPH scavenging activity) were observed in low amounts. Concerning methanolic extracts, rosmarinic acid was the most abundant polyphenol (1.70-9.85mg/g), followed by methoxysalicylic acid, apigenin, kaempferol and luteolin.